Social attitudes of educational agents towards inclusion and training in applied behavior analysis - Benitez, Priscila; Paulino, Vanessa Cristina; Oliveira, Ailton Paulo; Domeniconi, Camila; Omote, Sadao [UNESP] (FapUNIFESP (SciELO), 2021)
The social attitudes of educational agents can influence the development of inclusive practices in the school context. Considering the main challenges of school inclusion of students with Autism Spectrum Disorder (ASD) in the regular school system, this research aimed to evaluate the social attitudes of formal and informal educational agents concerning inclusion, before and after a program of training in Special and Inclusive Education, based on the Applied Behavior Analysis. Fifty-two educational agents participated. The program was composed of meetings for theoretical discussions, practical activities, and guided reading on Special and Inclusive Education and analytical-behavioral strategies for intervention. Social attitudes toward inclusion were measured through the Likert Scale of Social Attitudes toward Inclusion before and after the training. Wilcoxon’s test revealed a statistically significant difference between the pre-test scores and post-test scores (p = 0.003). The implications of the proposed training program on the possibilities for the development of an inclusive school environment were discussed, since this training resulted in more favorable social attitudes of the educators toward inclusion.
Atitudes sociais de agentes educacionais em relação à inclusão e à formação em análise do comportamento aplicada
Keywords: Applied behavior analysis; Autism spectrum disorder; Educational agents; Inclusion; Social attitudes